A Call for the Empirical Investigation of Tear Stimuli - Krivan, Sarah J.; Thomas, Nicole A. (Frontiers in Psychology, 2020)
Emotional crying is a uniquely human behaviour, which typically elicits helping and empathic responses from observers. However, tears can also be used to deceive. ‘Crocodile tears’ are insincere tears used to manipulate the observer and foster prosocial responses. The ability to discriminate between genuine and fabricated emotional displays is critical to social functioning. When insincere emotional displays are detected, they are most often met with backlash. Conversely, genuine displays foster prosocial responses. However, the majority of crying research conducted to date has used posed stimuli featuring artificial tears. As such it is yet to be determined how the artificial nature of these displays impact person perception. Throughout this article, we discuss the necessity for empirical investigation of the differences (or similarities) in responses to posed and genuine tearful expressions. We will explore the recent adoption of genuine stimuli in emotion research and review the existing research using tear stimuli. We conclude by offering suggestions and considerations for future advancement of the emotional crying field through investigation of both posed and genuine tear stimuli.